7(-8+2m)-3m=

Simple and best practice solution for 7(-8+2m)-3m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(-8+2m)-3m= equation:


Simplifying
7(-8 + 2m) + -3m = 0
(-8 * 7 + 2m * 7) + -3m = 0
(-56 + 14m) + -3m = 0

Combine like terms: 14m + -3m = 11m
-56 + 11m = 0

Solving
-56 + 11m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + 11m = 0 + 56

Combine like terms: -56 + 56 = 0
0 + 11m = 0 + 56
11m = 0 + 56

Combine like terms: 0 + 56 = 56
11m = 56

Divide each side by '11'.
m = 5.090909091

Simplifying
m = 5.090909091

See similar equations:

| 78=6x+6x-6 | | ln(x-2)+5=7 | | 15x-3(3x-2)=45-5(2x-5) | | 5(-6f-9)= | | .5k+2=5+8.3k | | 2(12-x)=-76-x | | -6k-8(3+7k)= | | 60=-2x+7x+5 | | 6(-2w-4)= | | log(x+12)+log(X-3)=2 | | -8(-7-3r)= | | -4(5-6d)+2= | | 2x+(-4x)-x=0 | | 23=7x+6x+10 | | -7-2(9-4g)= | | (2x-5)2-(x-6)2=80 | | 9(7p-8)= | | 5x-2=5x+12 | | 8(-5y-9)+6= | | 29+x(x-4)=(x+3)2 | | 6(-7+9k)= | | -540.00+13.5x=4158 | | -540.00+13.5x=1500 | | 100=1.8c+32 | | 9-3x+7x=-15 | | 1/2+5/3= | | 16t^2-128t=0 | | Y=x+7sqrt(x)-18 | | 3x^2-15x+72=0 | | 2x-33=37 | | 2x-23=24 | | -2x=96 |

Equations solver categories